Moving inclusion forward for students with special educational needs in the Asia-Pacific region - Beamish, Wendi; Hay, Stephen; Yuen, Mantak (Frontiers in Education, 2024)
This paper draws on a comparative study of seven jurisdictions in the Asia-Pacific region to examine current challenges to progressing inclusive education for students with special educational needs (SEN) in mainstream schools. The study used a qualitative approach to collect data from each jurisdiction through a purposive sampling of knowledgeable, university-associated informants. Content analysis was used to identify and quantify specific challenges reported in the data. Subsequently, these items were coded as themes to form a matrix of challenges within and across jurisdictions. Findings revealed that challenges were broadly consistent with recent global trends and shared many commonalities, despite occurring in diverse societal, political and education systems. These challenges are: lack of adequate initial teacher education and ongoing professional development for practicing teachers; lack of resources and support to meet the needs of students with SEN; inconsistent policy guidelines and implementation action plans; restricted stakeholder engagement and collaboration across all levels of education; and limited local inclusion research to inform practice in schools. The findings underscore the need for government and institutional commitment and oversight to bridge the policy-to-practice gap, and an urgent need for local research to identify and disseminate successful approaches for including students with SEN throughout the region.